American myth and the legacy of Vietnam - Hellmann, John, 1948- (New York : Columbia University Press, 1986)
Includes critical estimates of such novels as The ugly American, by William Lederer and Eugene Burdick, and The Green Berets, by Robin Moore; and such films as The deer hunter and Apocalypse now.
"An angry dream": the Cold War, Southeast Asia, and the American mythic landscape -- The return of the frontier hero: national purpose and the legend of the Green Berets -- The antiwar movement and the frontier -- Good sons: the soldiers' antimyth -- The hero seeks a way out -- Epic return -- Toward new myth.
Includes index.
Bibliography: p. [225]-233.
Keywords: Vietnam War, 1961-1975 -- United States; Vietnam War, 1961-1975 -- Influence; National characteristics, American; Vietnam War, 1961-1975 -- Literature and the war; Vietnam War, 1961-1975 -- Motion pictures and the war